PERSEPSI GURU BIDANG STUDI TERHADAP KINERJA GURU BIMBINGAN DAN KONSELING KOTA TAKENGON - Zahra, Refina Athira; Bahri, Syaiful; Rahmiyati, Evi (Realita : Jurnal Bimbingan dan Konseling, 2026)
This study aims to describe subject teachers’ perceptions of the performance of Guidance and Counseling (GC) teachers in Takengon City. The background of this study is the importance of subject teachers’ perceptions of GC teachers’ performance, particularly in relation to service planning, service implementation, as well as evaluation and follow-up of guidance and counseling services. This research employed a descriptive quantitative method. The research sample consisted of 240 subject teachers from schools in Takengon City. Data were collected through a Likert-scale questionnaire developed based on the performance aspects of guidance and counseling teachers. Data were analyzed using descriptive percentage analysis. The results of the study indicate that subject teachers’ perceptions of GC teachers’ performance in Takengon City fall into the Very Good category, with an average percentage of 75.33%, covering aspects of service planning, service implementation, as well as evaluation and follow-up of guidance and counseling services. The conclusion of this study is that the performance of guidance and counseling teachers in Takengon City is perceived as very good by subject teachers. This study is expected to serve as evaluation material and provide input for guidance and counseling teachers in improving the quality of guidance and counseling services in schools.